Evaluation of Employee Performance in the Satker for the Development of a Settlement Environmental Sanitation System - Roylen H. Zakaria; Nuzlan Botutihe; Robin Pakudu (Journal La Sociale, 2022)
The purpose of this study was to determine the implementation of employee evaluation in the Gorontalo Settlement Environmental Sanitation System Development Working Unit. This study uses a descriptive method with a qualitative approach. The results showed that in evaluating the performance of employees at the Gorontalo Settlement Environmental Health Development Work Unit, these five dimensions were included. From the results of the study, it was concluded that the evaluation of employee performance at the Gorontalo Settlement Environmental Health Development Work Unit had not gone well. However, from the five indicators according to Robbins (2016: 260), work quality is important, but according to Robbins (2016: 260) it is still in the poor category due to the lack of awareness of employees or officials in terms of maximizing the quality of performance, this is one of the mistakes. one obstacle in the realization of each program.